Proteomic analysis of whole blood to investigate the therapeutic effects of nervonic acid on cerebral ischemia-reperfusion injury in rats - Qingqing Li; Fengrong Zhang; Xianyu Li; Qing Wang (Frontiers in Cell and Developmental Biology)
IntroductionBlood proteomics offers a powerful approach for identifying disease-specific biomarkers. However, no reliable blood markers are currently available for the diagnosis stroke. Nervonic acid (NA), a vital long-chain monounsaturated fatty acid found in mammalian nervous tissue, shows promising therapeutic potential in neurological disorders. This study aimed to develop a reliable methodology for whole blood proteomics to identify early warning biomarkers and evaluate drug treatment efficacy.MethodsAfter modeling via the classic thread embolization method, whole blood samples were collected from the rats. Morphological assessments of brain tissue indicated that NA significantly mitigated brain and neuronal damage in rats. The differential protein expression profile was analyzed using Liquid Chromatography—Tandem Mass Spectrometry (LC-MS/MS) whole blood proteomics.ResultsZZZGene Ontology (GO) analysis revealed that, compared to ginkgo biloba extract (EGb), the proteins differentially expressed under NA intervention were predominantly involved in oxidative stress response and calcium-dependent adhesion processes. Key targets of NA in the treatment of middle cerebral artery occlusion (MCAO) models included ENO1, STAT3, NME2, VCL, and CCT3.DiscussionThis whole blood proteomic approach provides a comprehensive understanding of protein profiles associated with disease states, offering valuable insights into potential therapeutic targets and enabling the evaluation of NA and EGb intervention efficacy. Our findings underscore the protective effects of NA against cerebral ischemia-reperfusion injury and highlight its potential as a treatment for stroke.